It's time to foster Pride and let go of Prejudice. Disability Pride Month: Why Pakistan needs it? - Siddiqui, Rida Asim (Journal of the Pakistan Medical Association, 2023)
Respected Madam, Since the beginning of time, disability, in any form, has always had an enormous amount of stigma attached to it and Persons with Disabilities (PWDs) are made to suffer hardships and injustices every day. Pakistan has a population of roughly 207 million people.1 Around 31 million people in Pakistan are anticipated to be living with a disability. According to the disability evaluation report conducted by Pakistan Poverty Alleviation Fund (PPAF), eight out of every 100 people have a handicap of some kind, and one out of every 130 people has a severe condition.2 July celebrates the Disability Pride Month honouring the signing of the Americans with Disabilities Act, which occurred 32 years ago.3 Yet, this day has a deeper meaning; This month empower PWDs to proudly own their identities and reinvent the power dynamic designed to work against them. PWDs in Pakistan are often marginalized, made to feel inferior, and rarely seen actively participating in society alongside those who can. Our community still has archaic views such as, disability is a source of shame for the family, a form of punishment for crimes, and a detachment from religion.4 According to estimates, 24.9 to 41% of persons with disabilities experience depression, compared to 22.8 to 27.5% of adults without disabilities.5 Madam, this is a painful reality, but we must face it together. All of these injustices have left Pakistani PWDs feeling lost and disempowered. When they are constantly let down and made to feel inferior, it demoralizes them before they can muster the courage and determination to seek opportunities and demand justice. Pakistan desperately needs Disability Pride Month as a platform and reminder that every member of society, able-bodied or not, is equally important and has something unique to offer. Given that Pakistan is a developing country and that the government frequently overlooks their fundamental rights and demands, Disability Pride Month will allow them to celebrate all that they have overcome and accomplished, providing them a platform to draw attention to their issues and shed light on their concerns. A revolutionized change can occur in the practices of this archaic society. Awareness is essential, but Pride stems from within. A man who has faith in himself will strive to conquer his goals. That is when a true change will occur.